Small donors for small recipients – excellent growth and long‐term function of single kidney grafts. (3rd November 2021) - Cetiner, Metin; Paul, Andreas; Treckmann, Juergen W.; Dittmann, Susanne; Büscher, Rainer; Hoyer, Peter F.; Büscher, Anja K.
Summary: Small‐donor kidneys (≤20 kg donor weight, SDK) are preferably transplanted en bloc in adults. Concerns about thrombotic complications or hyperfiltration hinder their use in children, particularly as single grafts. Low centre experience and donor‐to‐recipient size are rated critical regarding outcomes. We evaluated SDK transplantation (SDTx) in paediatric recipients at a specialized transplant centre. Between 2008 and 2018, SDTx was performed in 40 children (mean age 5.4 ± 1.4 years, single grafts n = 38, donor weight ≤10 kg: n = 10). Perioperative complications were rare ( n = 3), mainly thromboses despite immediate heparinization and resulted in graft loss in one patient. Overall, early and long‐term GFR were excellent (76 ± 21 and 100 ± 11 ml/min/1.73 m 2, first month and year 5, respectively). Three patients presented with delayed graft function. Graft volume increased significantly (69 ± 38 vs. 111 ± 33 ml within 5 years; P < 0.0001). Patients showed catch‐up growth to normal range (SDS for height −2.06 ± 1.6 to −1.60 ± 1.5). Stratification by recipient age and donor weight revealed superior results in young recipients (≤3 years) and ≤10 kg donors, respectively. Outcome of single SDK grafts was excellent. Gain of GFR and graft volume was even higher in patients with very small donor or recipient size, regardless of a reduced donor‐to‐recipient weight ratio. Therefore, SDTx should be considered favouring small paediatric recipients. Abstract : Outcome of small‐donor kidney transplantation in children was excellent, especially in case of very small donor or recipient size. It was not impaired by high perioperative complication rates, low early graft function, or single grafts and therefore should be pursued in specialized centres.